A handbook for support workers in health and social care : a person-centred approach - Mackreth, Paul (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Support workers are key deliverers of care in the UK, often hugely valued by those people they provide care for. Their roles and responsibilities are increasing in the midst of ever-changing health and social care systems. A Handbook for Support Workers in Health and Social Care recognises the contribution of support worker and provides an introduction to the core knowledge, legislation and models of practice required to work across health and social care settings. Covering core person-centred skills that a support worker needs to develop, this textbook looks at knowing and managing yourself, before moving on to understanding your role in the organisation and teamwork. It outlines the relevant legislation and policies from confidentiality to infection control. Communication - both written and in person - is a central theme and key values such as compassion and dignity are explored in relation to this. There is a thought-provoking discussion of working with people, with topics covered including respecting choices, thinking about risk and safeguarding. The book ends by looking at what it means to be a competent practitioner and the importance of continual professional development. The first textbook introducing core theory and practice knowledge necessary to work as support worker in health and social care, it includes case studies, tasks and exercises to help the reader apply their learning"--
OCLC-licensed vendor bibliographic record.
Keywords: Allied health personnel -- Great Britain; Social service -- Great Britain; MEDICAL / Nursing / Fundamentals & Skills; MEDICAL / Allied Health Services / General